Peran Kepala Sekolah Dalam Meningkatkan Mutu Pendidikan Di Madrasah Aliyah NW Penendem - Muhamad Zaril Gapari; Qusyairi, Lalu A. Hery; Siasatwika, Rauhun (Aslamiah : Jurnal Pendidikan, Ekonomi, Sosial dan Budaya, 2023)
Headmaster as a leader is an accepted metaphor in general, with the teacher as a follower or the teacher as a worker. later This is more Lots the educational reform literature consistently emphasize that effective leader No apply in a manner directly, but are very influential on the ability of madrasas to increase the quality implementation of programs and the success of the academic student. Study This aim For know Study This aim is for, 1) knowing the leadership head school, 2) quality education at Madrasah Aliyah NW Penendem, 3) and roles head school in increasing the quality of input, process, and output. Research type This is a study qualitative and the approach used is approach qualitative descriptive. As an informant in the study, This is the head school, deputy head of curriculum, treasurer, and TU staff. Data collection was carried out with three methods that are, method observation, interview, and documentation. Research results This show that, the role of the Head Schools in Improving the Quality of Education at Madrasah Aliyah NW Penendem is with way, set up professional educators, provide an environment conducive to learning, make appropriate programs with need student as well as and give motivation to learn. Head role school in increase input quality ie by preparing professional educators, in increase process quality ie with provide an environment conducive to learning For activity learning, in increase quality results that is with reach quality graduates.